Analysis of Episodes of Care in Medicare Beneficiaries Newly Diagnosed with Alzheimer's Disease. Issue 5 (30th March 2018) - Khandker, Rezaul K.; Black, Christopher M.; Xie, Lin; Kariburyo, M. Furaha; Ambegaonkar, Baishali M.; Baser, Onur; Yuce, Huseyin; Fillit, Howard
Abstract : Objectives: To study transitions between healthcare settings and quantify the cost burdens associated with different combinations of transitions during a 6‐month period before initial Alzheimer's disease (AD) diagnosis so as to investigate how using an episode‐of‐care approach to payment for specific disease states might apply in AD. Design: A retrospective observational cohort study. Setting: United States. Participants: A random sample of 8, 995 individuals aged 65 to 100 with a diagnosis of AD ( International Classification of Diseases, Ninth Revision, Clinical Modification code 331.0) were identified from the Medicare database between January 1, 2011, and June 30, 2014. This analysis identified individuals with AD diagnosed in inpatient (18%), skilled nursing facility (SNF) (1%), hospice (4%), and home and outpatient (77%) settings and analyzed episodes that began in the index setting (defined as the care setting in which the individual was first diagnosed with AD). Measurements: Study outcomes included number of transitions between settings, primary discharge diagnoses, and total all‐cause healthcare costs during the 6 months after the AD diagnosis. Results: The average numbers of transitions between care settings were 2.8 originating from an inpatient setting, 2.4 from a SNF, 0.3 from a hospice setting and 0.7 from a home or outpatient setting during 6 months post‐AD diagnosis. The overall cost burden during the 6 months after AD diagnosis (including costs incurred at the index setting) was high for individuals diagnosed in a nonambulatory setting (mean $41, 468). Individuals diagnosed in an ambulatory setting incurred only $12, 597 in costs during the same period. Conclusion: Episodes of care can be defined and studied in individuals with AD. An episode‐of‐care approach to payment could encourage providers to use the continuum of care needed for quality medical management in AD more efficiently.